Foliar nutrients of second crop corn submitted to basalt and animal residues - Ribeiro , Luane Laíse Oliveira; Seidel , Edleusa Pereira; Almeida , Karlene Fernandes de; Kappes, Nathalia Maísa; Sustakowski, Monica Carolina; Reis, Willian dos; Carvalho , Alysson Oliveira de; Mottin , Marcos Cesar; Cruz, Maria Soraia Fortado Vera; Oliveira, Paulo Sérgio Rabello de (Seven Editora, 2024)
The use of basalt used with animal residues can be an efficient alternative for fertilization for corn crops. The objective of this study was to evaluate the effect of doses of basalt powder with cattle manure and chicken litter on the nutritional content of the leaves of the second corn crop, using soluble chemical fertilization (NPK) as a reference. The experiment was carried out in DBC  with factorial arrangement (5 x 2) + 1, in four replications, using five basalt doses (0, 4, 8, 12 and 16 t ha-1) associated with cattle manure and chicken litter and an additional treatment with soluble chemical fertilization (NPK). The leaf contents of N, P, K, Ca and Mg were evaluated. The nutrients N, P, K of corn cultivated with basalt doses and animal residues did not show significant differences. The leaf Ca and Mg contents of the two residues showed positive responses. The use of basalt in association with residues provided responses equivalent to those obtained with the use of soluble chemical fertilization, and these inputs can be indicated for use in agriculture to contribute to the sustainability of agricultural systems. DOI:https://doi.org/10.56238/sevened2023.006-123